2010
DOI: 10.3171/2010.1.jns091740
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality among neurosurgeons

Abstract: Object The authors sought to determine a cause-specific mortality profile for US neurosurgeons during the period 1979–2005. Methods Neurosurgeons who died during the study period were identified from the Physician Master File database. Using the National Death Index, the reported cause of death was identified for 93.7% of decedents. Standardized mortality ratios were used to compare mortality risk in the study cohort to that of the US population. Results There was a marked reduction in mortality from virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Both body and mind are affected negatively. 7 Certain tools used by neurosurgeons too, can invite problems. The virtual 3D vision created by microscope, weakens a neurosurgeon's accommodation reflex after prolong hours of usage.…”
Section: Neurosurgeons Are Humans They Too Are Falliblementioning
confidence: 99%
“…Both body and mind are affected negatively. 7 Certain tools used by neurosurgeons too, can invite problems. The virtual 3D vision created by microscope, weakens a neurosurgeon's accommodation reflex after prolong hours of usage.…”
Section: Neurosurgeons Are Humans They Too Are Falliblementioning
confidence: 99%
“…In 2 epidemiological studies conducted among healthcare personnel, no increased risk for leukemia was shown for the group of nurses [81] and neurosurgeons [83] while the findings of a third study which has shown increased mortality from CLL among nurses may be strongly affected by overdiagnosis of the disease due to the increased health awareness of the specific group [82]. Furthermore, a number of ecological-design studies have recorded a statistically significant excess risk of leukemia among specific categories of workers which include women (other than nurses) working in the healthcare sector [89], workers whose tasks involve exposure to Polychlorinated Biphenyls (PCBs) and printing inks [91], workers exposed to benzene or pesticides or working near high voltage lines [92], workers in plastic production, cleaning and construction work [93], and several categories of workers in the agricultural sector i.e.…”
Section: Reviewmentioning
confidence: 99%
“…It suggests neurosurgeons to have a more than 2-fold risk of death from AD. 65 Is the exposure to patient brain responsible for that finding or are there alternative explanations? First of all, careful assessment of potential biases is necessary.…”
Section: Problems To Address In Epidemiological Studiesmentioning
confidence: 99%